The usefulness of mesocosms for ecotoxicity testing with lacertid lizards - Amaral, Maria José (2019)
Mesocosms (i.e., outdoor, man-made representations of natural ecosystems) have seldom been used to study the impact of contaminants on terrestrial ecosystems. However, mesocosms can be a useful tool to provide a link between field and laboratory studies. We exposed juvenile lacertid lizards for a period of over one year to pesticides (herbicides and insecticides) in mesocosm enclosures with the intention of validating field observations obtained in a previous study that examined the effects of corn pesticides in Podarcis bocagei. Our treatments replicated field conditions and consisted of a control, an herbicides only treatment (alachlor, terbuthylazine, mesotrione and glyphosate) and an herbicides and insecticide treatment (including chlorpyrifos). We used a multi-biomarker approach that examined parameters at an individual and sub-individual level, including growth, locomotor performance, standard metabolic rate, biomarkers of oxidative stress, esterases and liver histopathologies. Although mortality over the course of the exposures was high (over 60%), surviving individuals prospered relatively well in the mesocosms and displayed a broad range of natural behaviours. The low numbers of replicate animals compromised many of the statistical comparisons, but in general, surviving lizards exposed to pesticides in mesocosm enclosures for over one year, thrived, and displayed few effects of pesticide exposure. Despite the difficulties, this work acts as an important stepping-stone for future ecotoxicology studies using lizards.